Combined High Irradiance and Water Deficit Alters the Anatomy and Physiology of Photomorphogenic Mutant Micro-Tom Plants - Ariana Bertola Carnevale; Alan Carlos da Costa; Emily Carolina Duarte Santos; Adinan Alves da Silva; Priscila Ferreira Batista; Fábia Barbosa da Silva; Luciana Minervina de Freitas Moura; Caroline Müller (Agriculture, 2025)
Plants are continuously exposed to multiple environmental stressors throughout their lifecycle. Understanding their integrated physiological, biochemical, and anatomical responses under combined stress conditions is crucial for developing effective approaches to improve stress tolerance and maintain crop productivity. This study aimed to investigate the physiological, biochemical, and anatomical changes in photomorphogenic Micro-Tom plants exposed to high irradiance and water deficit—an abiotic stress combination that commonly co-occurs in natural environments but remains poorly understood in light-sensitive genotypes. We hypothesized that the high pigment 1 (hp1) mutant, due to its enhanced light responsiveness, would display improved stress acclimation compared to the wild-type when exposed to combined stress factors. This study was conducted in a controlled plant growth chamber, using a randomized block design with five replicates. Two Micro-Tom genotypes (wt and hp1) were exposed to control (soil at field capacity (FC) + 450 μmol m−2 s−1 PPFD) and combined stress (40% FC + 1800 μmol m−2 s−1 PPFD) conditions. Despite the higher concentration of chloroplast pigments in hp1, its photosynthetic performance under combined stress was not significantly improved, and its defense mechanisms did not effectively mitigate the stress impacts. Anatomically, wt exhibited greater structural adjustment, observed by adaptations in the spongy parenchyma and mesophyll. Overall, the wt genotype showed stronger defense mechanisms, while hp1 was more susceptible to combined abiotic stress.